Analyzes the Dynamic Capabilities and Measure its Effect on Strategic Agility: Applied Study in Asiacell- Telecommunications Company - Mansoor, Hamdan; Yakoob, Najwa (The Arab Journal of Administration, 2021)
Based on the literature of Dynamic Managerial Capabilities (DMC), which has in turn been derived from the Resource Based-View (RBV), this paper aimed at analyzing the relationship between dynamic capabilities and measuring their impact on the strategic agility using linear regression, multiple linear regression and linear correlation coefficient. The dynamic capabilities have been analyzed into three main dimensions (Resource Integration, Resource Reconfiguration, and Strategic Learning) to measure their impact on the organization’s strategic agility with its dimensions (Strategic sensitivity, Resource Fluidity, Collective Commitment), as it is considered the appropriate approach by which organizations respond to businesses environmental change within their work and their strive to survive. The study concluded many findings, the most prominent one is that dynamic capabilities are significantly associated with and affect the organization strategic agility dimensions. In addition, the configuration and deployment capabilities of the investigated company have indicated higher impact and association with its strategic agility. Accordingly, some suggestions have been made that would have contributed to encourage organizations to support dynamic capabilities for using as an appropriate resource as being strategically ready to respond, which enhance their abilities to adapt to business changes, hence sustained competitive responses of the examined companies.